2019
DOI: 10.21608/jesp.2019.68080
|View full text |Cite
|
Sign up to set email alerts
|

Entomological Surveillance of Aedes Aegypti and Arboviruses Outbreak of Dengue Fever in the Red Sea Governorate, Egypt

Abstract: were selected for entomological surveys where dengue fever was anticipated to be occurred at November 2017. A total number of 469 houses were participates survived, positive adult houses were 20.47% (96/469), while positive larvae houses were 10.23 % (48/469). The stogmoyia indices for the parameters of house index (HI), container index (CI) and Breteau index (BI) were (10.2, 7.0 &16) respectively. The survey yielded a total number of immature stages of Aedes aegypti of 92.22% (960/1041), or 92.5 % (888/960) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The outcome results of Mostafa's study showed that the Red Sea Governorate has a high prevalence of Ae. aegypti and consequently a potentially increasing incidence of dengue fever [34].…”
Section: Denguementioning
confidence: 99%
“…The outcome results of Mostafa's study showed that the Red Sea Governorate has a high prevalence of Ae. aegypti and consequently a potentially increasing incidence of dengue fever [34].…”
Section: Denguementioning
confidence: 99%
“…In addition, field-based vector surveillance revealed the presence of Ae . aegypti larvae and adult mosquitoes at the patients’ dwellings [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%